30 great myths about the Romantics - Wu, Duncan (Malden, MA : John Wiley & Sons Inc., 2015)
"Wu is not a scholar who trades in faddish or modish opinion, and as its title implies, this is by its very nature an exercise in controversy and debate. The book represents a triumph of individual scholarship over what is claimed as often flawed, albeit consensual, critical opinion. Wu's fluid, readable prose is accessible to all, and his extensive and subtle insights are a joy to read. This unique addition to the student bookshelf provides enjoyment and instruction simultaneously."-- Jane Moore, Cardiff University.
Myth 29 The Romantics practised free love on principleMyth 30 The Romantics were the rock stars of their day; Coda; Further Reading; Index; EULA.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: 1700-1899; English literature -- 19th century -- History and criticism; English literature -- 18th century -- History and criticism; Romanticism -- Great Britain; Literature and society -- Great Britain -- History; English literature -- 18th century -- History and criticism; English literature -- 19th century -- History and criticism; Literature and society -- Great Britain -- History; Romanticism -- Great Britain; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English literature; Literature and society; Romanticism; Great Britain; Electronic books; Criticism, interpretation, etc; History